Nickel-based alloy with excellent high-temperature thermal fatigue performance and preparation method

CN122941930APending Publication Date: 2026-10-20JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611041162.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

现有技术多通过调控Zr、Hf或稀土等高成本金属元素改善镍基高温合金性能,其作用主要体现在固溶强化、γ′相强化或晶界强化;本发明未采用Zr、Hf或稀土等贵金属元素,并且二硼化铌纳米陶瓷颗粒作为强化相引入镍基合金基体中质量占比≤0.09%,因此能够大幅降低原料成本。在微观组织方面,现有技术主要通过调控γ′相析出位置,改善组织稳定性;本发明通过二硼化铌纳米颗粒与镍基合金基体之间的组分相互作用,并协同调控组分配比、制备工艺及工艺参数,使二硼化铌纳米颗粒在基体中稳定弥散分布,并实现如下作用1.颗粒成为异质形核核心,有效细化组织;2.通过界面钉扎抑制γ′相在20-800℃热循环过程中的粗化;3.提高γ′相体积分数,并且细化γ′强化相;因此在裂纹扩展过程中诱导裂纹钉扎、偏转或分叉,从而抑制裂纹扩展。在宏观性能方面,现有公开研究中的代表性镍基高温合金经20-800℃,2000次高温热疲劳测试后主裂纹长度可达到百微米量级,而本发明合金在20-800℃经最高2000-4000次热循环后,主裂纹长度仍控制在11.5μm以下,综上,与现有技术相比,本发明的裂纹萌生和扩展受到显著抑制,具有更优异的抗热疲劳损伤能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a nickel-based alloy with excellent high-temperature thermal fatigue performance and its preparation method. The preparation method mainly includes: mixing boron powder with cobalt-niobium alloy powder, followed by high-frequency induction plasma reaction and argon rapid cooling to obtain an intermediate alloy powder containing cobalt-coated niobium diboride nanoparticles; then adding the intermediate alloy powder to a nickel-based high-temperature alloy melt, followed by stirring, casting, homogenization, hot forging, solution treatment, and two-stage aging treatment to obtain a nickel-based alloy with excellent high-temperature thermal fatigue performance, in which niobium diboride nanoparticles are uniformly dispersed. After 2000-4000 thermal cycles at 20-800℃, the main crack length is 4.2-11.5 micrometers, exhibiting excellent high-temperature thermal fatigue performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance high-temperature alloy technology, specifically to nickel-based alloys with excellent high-temperature thermal fatigue properties and their preparation methods. Background Technology

[0002] Nickel-based superalloys are widely used in aero-engine turbine guide vanes, gas turbine hot-end components, and other high-temperature service components due to their excellent high-temperature strength, oxidation resistance, and corrosion resistance. However, these materials often experience frequent start-ups and shutdowns and drastic temperature changes during actual service, making them prone to thermal fatigue damage under cyclic thermal stress. This leads to crack initiation and propagation, which in turn reduces the load-bearing capacity of components, shortens service life, and in severe cases, even causes fracture failure.

[0003] To improve the high-temperature thermal fatigue performance of nickel-based superalloys, existing technologies typically employ methods such as composition optimization, microalloying, grain boundary engineering, and heat treatment process optimization. For example, the matrix strength is increased by controlling the content of strengthening elements and precipitated phases; grain boundary bonding and oxidation resistance are improved by adding Zr, Hf, and rare earth elements; and the morphology of the γ′ strengthening phase and grain boundary structure are optimized through heat treatment, all in order to enhance the alloy's resistance to thermal fatigue.

[0004] However, existing technologies still have shortcomings. From a composition design perspective, while elements such as Zr, Hf, and rare earth elements can improve high-temperature performance to some extent, they typically suffer from high raw material costs, difficulty in controlling composition, and the potential to introduce segregation or harmful brittle phases. From a process perspective, existing technologies often rely on complex heat treatment processes, resulting in complex manufacturing processes and poor stability. From a microstructure perspective, under long-term thermal cycling conditions, the γ′ strengthening phase is still prone to coarsening, grain boundary structures are easily weakened, and the thermal stability of the microstructure is insufficient. From a performance perspective, existing technologies have limited effectiveness in suppressing the initiation and propagation of thermal fatigue cracks, especially primary cracks. Current reports indicate that commercially available nickel-based superalloys, under high-temperature thermal fatigue conditions, exhibit primary crack lengths on the order of hundreds of micrometers after 2000 thermal cycles, making it difficult to balance cost, process feasibility, and high-temperature thermal fatigue performance.

[0005] Therefore, how to reduce the amount of precious or rare earth elements added, control the cost of raw materials, and reduce the complexity of the process, so as to simultaneously improve the microstructure and thermal stability of nickel-based superalloys and effectively suppress the initiation and propagation of thermal fatigue main cracks, is a technical problem that urgently needs to be solved. Summary of the Invention

[0006] To solve the above-mentioned technical problems, this invention provides a nickel-based alloy with excellent high-temperature thermal fatigue performance, and its preparation method is as follows: (1) Boron powder and cobalt-niobium alloy powder are mixed at a mass ratio of 13-16:24-27 at a rotation speed of 90-120 r / min for 6-12 h to obtain powder mixture A; the particle size of the cobalt-niobium alloy powder is 30-220 micrometers and the particle size of the boron powder is 3-25 micrometers. (2) The powder mixture A obtained in step (1) is sent into a high-frequency induction plasma device and subjected to plasma reaction under pure argon protection. Finally, after argon rapid cooling treatment, intermediate alloy powder B containing cobalt-coated niobium diboride nanoparticles is obtained. The plasma reaction has the following characteristics: reaction pressure of 0.08-0.15 MPa, reaction temperature of 4800-5200℃, output power of 15-95 kW, and power supply operating frequency of 1.7-6.9 MHz; the cobalt-coated niobium diboride nanoparticles contained in the intermediate alloy powder B have an average particle size of 40-120 nanometers. (3) The nickel-based high-temperature alloy is heated to 1490–1530℃ under vacuum to form an alloy melt; the alloy melt is mixed with the intermediate alloy powder B obtained in step (2), and then melted and stirred at 1530℃–1680℃. After casting under argon protection, a nickel-based alloy ingot containing niobium diboride nanoparticles is obtained. The stirring speed is 350–650 r / min and the stirring time is 6–20 min. The mass ratio of the intermediate alloy powder B to the alloy melt is 0.009–0.1 wt.%:1; (4) The nickel-based alloy ingot containing niobium diboride nanoparticles obtained in step (3) is subjected to homogenization treatment, hot forging, solution treatment and two-stage aging treatment in sequence to obtain a nickel-based alloy with excellent high-temperature thermal fatigue performance. The homogenization process involves holding the temperature at 1160–1195℃ for 4–10 hours. The hot forging is carried out at 1050–1130°C with a forging ratio of 10–16:1. The solution treatment involves holding at 1120–1180℃ for 50–120 minutes followed by water cooling. The two-stage aging treatment involves holding at 760–820℃ for 6–12 hours followed by air cooling, and then holding at 650–720℃ for 10–24 hours followed by air cooling. The nickel-based alloy with excellent high-temperature thermal fatigue performance exhibits superior thermal fatigue properties at high temperatures. By mass percentage, it is composed of the following components: C: 0.01–0.09%; Cr: 16.0–25.0%; Co: 12.0–25.0%; Mo: 4.1–7.8%; W: 0.4–2.8%; Ti: 1.1–2.9%; Al: 0.10–0.95%; Fe: ≤1.6%; Mn: ≤0.80%; Si ≤0.90%; P ≤0.060%; S ≤0.070%; B: 0.03–0.08%; Nb: 0.025–0.085%; balance Ni. The nickel-based alloy with excellent high-temperature thermal fatigue performance contains niobium diboride nanoparticles with a size of 35-210 nm and a mass percentage of 0.01%-0.09%.

[0007] The nickel-based alloy exhibiting excellent high-temperature thermal fatigue performance, after 2000-4000 thermal cycles at 20-800℃, has a principal crack length of 4.2-11.5 micrometers. Thermal fatigue failure is mainly controlled by crack initiation and propagation, and the principal crack length is the main parameter characterizing thermal fatigue failure, directly affecting the service life of the material. The principal crack length typically increases with increasing temperature and the number of thermal cycles. Therefore, the principal crack length can effectively characterize the degree of thermal fatigue damage to the material and can serve as an important basis for evaluating the quality of thermal fatigue performance. The shorter the principal crack length, the better the thermal fatigue performance. Compared with the prior art, the principal crack length obtained by this invention is shorter, thus exhibiting better fatigue resistance.

[0008] Furthermore, the cobalt-niobium alloy powder in step (1) has a particle size of 60-200 micrometers and the boron powder has a particle size of 4-23 micrometers.

[0009] Furthermore, the plasma reaction described in step (2) has the following characteristics: reaction pressure of 0.09-0.14 MPa, reaction temperature of 4875-5125 °C, output power of 19-90 kW, and power supply operating frequency of 1.9-6.7 MHz; the average particle size of the niobium diboride particles in the intermediate alloy powder B is 42-115 nanometers.

[0010] Furthermore, the mass ratio of intermediate alloy powder B to alloy melt in step (3) is 0.035–0.07 wt.%:1.

[0011] Furthermore, the chemical composition of the nickel-based alloy with excellent high-temperature thermal fatigue performance described in step (4) is as follows (by mass percentage): C: 0.03–0.08%; Cr: 18.0–22.0%; Co: 15.0–22.0%; Mo: 4.5–7.5%; W: 0.5–2.5%; Ti: 1.6–2.8%; Al: 0.20–0.80%; Fe≤1.0%; Mn≤0.50%; Si≤0.50%; P≤0.020%; S≤0.010%; B: 0.03–0.075%; Nb: 0.026–0.083%; balance Ni.

[0012] The aforementioned nickel-based alloy with excellent high-temperature thermal fatigue performance contains niobium diboride nanoparticles with a size of 39-208 nm and a mass percentage of 0.015%-0.085%. Furthermore, the nickel-based alloy with excellent high-temperature thermal fatigue performance described in step (4) has a main crack length of 4.6-9.3 micrometers after 2500-3500 thermal cycles at 20-800℃.

[0013] Compared with the prior art, the advantages of the present invention are: Existing technologies mostly improve the performance of nickel-based superalloys by controlling high-cost metal elements such as Zr, Hf, or rare earth elements. Their effects are mainly reflected in solid solution strengthening, γ′ phase strengthening, or grain boundary strengthening. This invention does not use precious metal elements such as Zr, Hf, or rare earth elements, and the mass percentage of niobium diboride nano-ceramic particles introduced into the nickel-based alloy matrix as a strengthening phase is ≤0.09%, thus significantly reducing raw material costs. Regarding microstructure, existing technologies mainly improve microstructure stability by controlling the precipitation location of the γ′ phase. This invention utilizes the component interaction between niobium diboride nanoparticles and the nickel-based alloy matrix, and synergistically controls the component ratio, preparation process, and process parameters to achieve a stable and dispersed distribution of niobium diboride nanoparticles within the matrix. This achieves the following effects: 1. The particles become heterogeneous nucleation cores, effectively refining the microstructure; 2. Interfacial pinning inhibits the coarsening of the γ′ phase during thermal cycling at 20-800℃; 3. It increases the volume fraction of the γ′ phase and refines the γ′ strengthening phase. Therefore, it induces crack pinning, deflection, or bifurcation during crack propagation, thereby inhibiting crack propagation. In terms of macroscopic performance, representative nickel-based superalloys in existing publicly available research can have main crack lengths reaching the hundreds of micrometers after 2000 high-temperature thermal fatigue tests at 20-800℃. However, the alloy of this invention, after a maximum of 2000-4000 thermal cycles at 20-800℃, still has a main crack length controlled below 11.5μm. In summary, compared with the prior art, the crack initiation and propagation of this invention are significantly suppressed, and it has a superior resistance to thermal fatigue damage. Attached Figure Description

[0014] Figure 1The image shows the thermal fatigue crack pattern of nickel-based alloy 1 with excellent high-temperature thermal fatigue performance in Example 2 of this invention under 2000 thermal cycles at 20-800℃.

[0015] Figure 2 The image shows the thermal fatigue crack pattern of nickel-based alloy 2 with excellent high-temperature thermal fatigue performance in Example 3 of the present invention under 3000 thermal cycles at 20-800℃.

[0016] Figure 3 The image shows the thermal fatigue crack pattern of nickel-based alloy 3 with excellent high-temperature thermal fatigue performance in Example 4 of this invention under 4000 thermal cycles at 20-800℃.

[0017] Figure 4 The image shows the thermal fatigue crack pattern of the nickel-based alloy in Comparative Example 1 of this invention under 1000 thermal cycles at 20-800℃. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example 1

[0019] The preparation method of cobalt-coated niobium diboride nanoparticle intermediate alloy powder B is as follows: (1) Weigh boron powder and cobalt-niobium alloy powder at a mass ratio of 13.5:26, place the boron powder and the cobalt-niobium alloy powder in a closed mixer, and mix at a speed of 97 r / min for 9.2 h to obtain powder mixture A; The cobalt-niobium alloy powder has a particle size of 63 micrometers, and the boron powder has a particle size of 5 micrometers. (2) The powder mixture A obtained in (1) is sent into a high-frequency induction plasma device and plasma reaction is carried out under pure argon protection. Finally, after argon rapid cooling treatment, intermediate alloy powder B containing cobalt-coated niobium diboride nanoparticles is obtained. The plasma reaction has the following characteristics: reaction pressure is 0.09 MPa, reaction temperature is 5012℃, output power is 33 kW, and power supply operating frequency is 5.2 MHz; the intermediate alloy powder B contains cobalt-coated niobium diboride nanoparticles with an average particle size of 74 nanometers. Example 2

[0020] The preparation method of nickel-based alloy 1, which exhibits excellent high-temperature thermal fatigue properties, is as follows: The nickel-based high-temperature alloy raw material was placed in a vacuum induction melting furnace and heated to 1496°C under vacuum conditions to form an alloy melt. The intermediate alloy powder B obtained in (2) was added to the alloy melt and electromagnetically stirred at 1546°C with a stirring speed of 392 r / min and a stirring time of 7 min. Then, it was poured under argon protection and the ingot was subjected to homogenization treatment, hot forging and solution treatment and double-stage aging treatment in sequence to obtain a nickel-based alloy 1 with excellent high-temperature thermal fatigue performance. The mass ratio of the cobalt-coated niobium diboride nanoparticle intermediate alloy powder B to the nickel-based alloy is 0.045 wt.%:1; The composition of the nickel-based alloy 1 with excellent high-temperature thermal fatigue performance, by mass percentage, is as follows: C: 0.032%; Cr: 18.8%; Co: 15.9%; Mo: 4.6%; W: 0.8%; Ti: 1.64%; Al: 0.3%; Fe: 1.0%; Mn: 0.50%; Si: 0.49%; P: 0.02%; S: 0.0070%; B: 0.03%; Nb: 0.032%; balance Ni; The homogenization process was carried out at 1169°C for 6 hours. The hot forging was carried out at 1092°C with a forging ratio of 10:1. The solution treatment was followed by water cooling after being held at 1130℃ for 55 minutes. The two-stage aging treatment involves holding at 765℃ for 6 hours followed by air cooling. After holding at 656℃ for 11 hours, air cool. The nickel-based alloy 1 with excellent high-temperature thermal fatigue performance prepared in this embodiment contains niobium diboride nanoparticles with a size of 43 nm and a mass percentage of 0.04%. Under 2000 thermal cycles at 20-800℃, thermal fatigue cracks appear as follows... Figure 1 As shown, the length of the main crack is 4.3 micrometers. Example 3

[0021] The preparation method of nickel-based alloy 2, which exhibits excellent high-temperature thermal fatigue properties, is as follows: The nickel-based high-temperature alloy raw material was placed in a vacuum induction melting furnace and heated to 1509°C under vacuum conditions to form an alloy melt. The intermediate alloy powder B obtained in (2) was added to the alloy melt and electromagnetically stirred at 1549°C with a stirring speed of 429 r / min and a stirring time of 8.3 min. Then, it was poured under argon protection and the ingot was subjected to homogenization treatment, hot forging and solution treatment and double-stage aging treatment in sequence to obtain nickel-based alloy 2 with excellent high-temperature thermal fatigue performance. The mass ratio of the cobalt-coated niobium diboride nanoparticle intermediate alloy powder B to the nickel-based alloy is 0.06 wt.%:1; The composition of the nickel-based alloy 2 with excellent high-temperature thermal fatigue performance, by mass percentage, is as follows: C: 0.03%; Cr: 18.9%; Co: 15.2%; Mo: 5.6%; W: 1.3%; Ti: 1.6%; Al: 0.5%; Fe: 0.9%; Mn: 0.45%; Si: 0.08%; P: 0.015%; S: 0.0065%; B: 0.053%; Nb: 0.049%; balance Ni; The homogenization process was carried out at 1172℃ for 6.3 hours. The hot forging was carried out at 1103°C with a forging ratio of 11:1. The solution treatment was followed by water cooling after being held at 1136℃ for 61 min. The two-stage aging treatment involves holding the product at 768℃ for 6.5 hours followed by air cooling. After holding at 659℃ for 11.3 hours, air cool. The nickel-based alloy 2 with excellent high-temperature thermal fatigue performance prepared in this embodiment contains niobium diboride nanoparticles with a size of 51 nm and a mass percentage of 0.057%. Under 3000 thermal cycles at 20-800℃, thermal fatigue cracks appear as follows... Figure 2 As shown, the length of the main crack is 8.9 micrometers. Example 4

[0022] Nickel-based alloy 3, which exhibits excellent high-temperature thermal fatigue properties, is prepared as follows: The nickel-based high-temperature alloy raw material was placed in a vacuum induction melting furnace and heated to 1519°C under vacuum conditions to form an alloy melt. The intermediate alloy powder B obtained in (2) was added to the alloy melt and electromagnetically stirred at 1556°C with a stirring speed of 539 r / min and a stirring time of 9.8 min. Then, it was poured under argon protection and the ingot was subjected to homogenization treatment, hot forging and solution treatment and double-stage aging treatment in sequence to obtain a nickel-based alloy 3 with excellent high-temperature thermal fatigue performance. The mass ratio of the cobalt-coated niobium diboride nanoparticle intermediate alloy powder B to the nickel-based alloy is 0.075 wt.%:1; The composition of the nickel-based alloy 3 with excellent high-temperature thermal fatigue performance, by mass percentage, is as follows: C: 0.06%; Cr: 18.9%; Co: 15.9%; Mo: 6.2%; W: 1.5%; Ti: 1.7%; Al: 0.62%; Fe: 0.76%; Mn: 0.5%; Si: 0.07%; P: 0.009%; S: 0.008%; B: 0.068%; Nb: 0.069%; balance Ni. The homogenization process was carried out at 1182℃ for 7.2 hours. The hot forging was carried out at 1123°C with a forging ratio of 12:1. The solution treatment was carried out at 1156°C for 91 min and then water-cooled. The two-stage aging treatment involves holding at 798℃ for 7.6 hours followed by air cooling. After holding at 699℃ for 11.9 hours, air cool; The nickel-based alloy 3 prepared in this embodiment, exhibiting excellent high-temperature thermal fatigue performance, contains niobium diboride nanoparticles with a size of 62 nm and a mass percentage of 0.073%. Under 4000 thermal cycles at 20-800℃, thermal fatigue cracks appear as follows... Figure 3 As shown, the length of the main crack is 11.2 micrometers. Comparative Example 1

[0023] A nickel-based alloy, the preparation method of which includes the following steps: Nickel-based high-temperature alloy raw materials are placed in a vacuum induction melting furnace and heated to 1496°C under vacuum conditions to form an alloy melt. The melt is then electromagnetically stirred at 1546°C with a stirring speed of 392 r / min and a stirring time of 7 min. Subsequently, the melt is poured under argon protection. The ingot is then subjected to homogenization treatment, hot forging and solution treatment, and two-stage aging treatment to obtain a nickel-based alloy. The nickel-based alloy, by mass percentage, comprises: C: 0.032%; Cr: 18.8%; Co: 15.9%; Mo: 4.6%; W: 0.8%; Ti: 1.64%; Al: 0.3%; Fe: 1.0%; Mn: 0.50%; Si: 0.49%; P: 0.02%; S: 0.0070%; with the balance being Ni. The homogenization process was carried out at 1169°C for 6 hours. The hot forging was carried out at 1092°C with a forging ratio of 10:1. The solution treatment was followed by water cooling after being held at 1130℃ for 55 minutes. The two-stage aging treatment involves holding at 765℃ for 6 hours followed by air cooling. After holding at 656℃ for 11 hours, air cool. In this embodiment, a nickel-based alloy exhibits thermal fatigue cracking under 1000 thermal cycles at 20-800℃, as shown in the example. Figure 4 As shown, the length of the main crack is 22.6 micrometers.

[0024] Compared with Comparative Example 1, Examples 2-4 of this invention differ in that the preparation parameters used in Comparative Example 1 and Example 2 are exactly the same, except that Example 2 adds nanoparticles. Regarding the microstructure, the trace amounts of niobium diboride particles added in Example 2 can promote microstructure refinement in the nickel-based alloy and pin the γ′ strengthening phase and crack propagation path, thereby improving the thermal stability of the microstructure and hindering crack propagation. In terms of performance, the nickel-based alloy 1 exhibits excellent high-temperature thermal fatigue performance, with thermal fatigue cracks resembling those observed under 2000 thermal cycles at 20-800℃. Figure 1 As shown, compared to Comparative Example 1, thermal fatigue cracks (such as those observed in Example 1) under 20-800℃ and 1000 thermal cycles... Figure 4 As shown in the figure, under the same operating temperature as the comparative example but with twice the number of thermal cycles, the thermal fatigue main crack length of the present invention is significantly shortened, reduced by approximately 81%, which means that the present invention effectively suppresses crack propagation. Therefore, the high-temperature thermal fatigue performance of the nickel-based alloy 1 obtained in this embodiment is significantly better than that of the nickel-based alloy obtained in comparative example 1.

[0025] Example 3, compared to Comparative Example 1, incorporated additional nanoparticles and used different process parameters. The comparative analysis showed that the nickel-based alloy 2 prepared in Example 3, exhibiting excellent high-temperature thermal fatigue performance, showed thermal fatigue cracking (e.g., ...) under 3000 thermal cycles at 20-800℃. Figure 2 As shown), compared to Comparative Example 1, thermal fatigue cracks under 20-800℃ and 1000 thermal cycles (as shown) Figure 4 As shown in the figure, in Embodiment 3 of the present invention, under the same operating temperature as the comparative example but with twice the number of thermal cycles, the length of the main thermal fatigue crack of the present invention is still shorter than that of the comparative example 1, reduced by about 61%, and the present invention still effectively suppresses crack propagation. Therefore, the high-temperature thermal fatigue performance of the nickel-based alloy 2 obtained in this embodiment is significantly better than that of the nickel-based alloy obtained in the comparative example 1.

[0026] Example 4, compared to Comparative Example 1, incorporated additional nanoparticles and used different process parameters. The comparative analysis showed that the nickel-based alloy 3 prepared in Example 4 exhibited excellent high-temperature thermal fatigue performance, exhibiting thermal fatigue cracking (e.g., [missing information]) under 4000 thermal cycles at 20-800℃. Figure 3 As shown), compared to Comparative Example 1, thermal fatigue cracks under 20-800℃ and 1000 thermal cycles (as shown) Figure 4 As shown in the figure, in Embodiment 4 of the present invention, under the same operating temperature as the comparative example but with three times more thermal cycles, the length of the main thermal fatigue crack of the present invention is still shorter than that of the comparative example 1, reduced by about 50%. This embodiment significantly inhibits crack propagation. Therefore, the high-temperature thermal fatigue performance of the nickel-based alloy 3 obtained in this embodiment is significantly better than that of the nickel-based alloy obtained in the comparative example 1. Comparative Example 2

[0027] In 2020, Xu et al. reported on the topic "Influence of Sr and Ce on the High-Temperature Mechanical and Thermal Fatigue Properties of Nickel-Based Superalloys," which is indexed in CNKI. They prepared the target nickel-based superalloy by adding 0.5%-1.5% Sr and 0.3%-1.0% Ce rare earth elements. The composition, by mass percentage, was: C: 0.06%; Cr: 16.9%; Co: 13.3%; Mo: 4.7%; W: 0.96%; Si: 0.90%; P: 0.063%; S: 0.072%; Sr: 0.5-1.5%; Ce: 0.3-1.0%; balance Ni. Under 1000 thermal cycles at 20-800℃, the principal crack length was 17 μm.

[0028] Regarding raw materials, Comparative Example 2 improved thermal fatigue performance by adding 0.5%-1.5% Sr and 0.3%-1.0% Ce rare earth elements, while this invention did not use any rare earth elements for strengthening. Instead, it added trace amounts of niobium diboride nanoceramic particles (less than 0.09%) to form a nanoparticle dispersion strengthening system, which greatly reduced costs. In terms of microstructure, Comparative Example 2 mainly relied on Sr and Ce to improve grain boundary state and microstructure purity. This invention utilizes niobium diboride nanoparticles to promote heterogeneous nucleation, refine the microstructure, and inhibit γ′ high-temperature coarsening, and improves crack propagation resistance through crack pinning, deflection, and bifurcation. Regarding performance, the addition of rare earth elements in Comparative Example 2 resulted in a main crack length of 17 μm in this nickel-based superalloy under 1000 thermal cycles at 20-800℃. Compared to Comparative Example 2, the main crack lengths in Examples 2-4 of this invention are all shorter (as shown in Table 1). Therefore, compared with the prior art, the nickel-based superalloy obtained by the present invention has good high-temperature thermal fatigue performance, which meets the industrial requirements for the service performance of nickel-based superalloys.

[0029] Table 1 compares the high-temperature thermal fatigue properties of nickel-based alloys in the comparative examples and various embodiments. The component ratios and process parameters used in Examples 2-4 of this invention are different, and the high-temperature thermal fatigue performance obtained in each example is also different, but all are higher than the high-temperature thermal fatigue performance obtained by the prior art. This shows that the significant improvement in the high-temperature thermal fatigue performance of the nickel-based alloy after being strengthened by micro-nano ceramic particles is not accidental, nor is it determined by a certain component or process parameter, but is achieved through the interaction of components, component ratios, processes and process parameters. Moreover, the best technical effect can only be achieved within the scope of protection of the claims of this invention.

[0030] In summary, compared with existing technologies, this invention, without adding rare earth or other precious metals, significantly reduces raw material costs while simplifying the process. It utilizes micro-nano particles to strengthen nickel-based superalloys, achieving reduced raw material costs, simplified processes, and a significant improvement in the alloy's high-temperature thermal fatigue crack resistance. The main reasons include: First, the nanoparticles and elements exhibit good wettability and strong bonding at the matrix interface. Second, they effectively pin grain boundaries and dislocations, improving grain boundary crack resistance and reducing the accumulation of thermal cycling damage. Third, they refine and stabilize the strengthening phase, delaying coarsening and degradation during high-temperature cycling and reducing stress concentration. Compared with existing technologies, the main crack length obtained in this invention is shorter, resulting in better fatigue resistance, effectively inhibiting crack initiation and slowing crack propagation. Furthermore, the number of cracks in this invention is far less than that in existing technologies, exhibiting a diffuse distribution, while existing technologies show a dense distribution. Therefore, this invention can significantly extend the service life of components under high-temperature start-up and shutdown and temperature alternation conditions, reduce the risk of sudden failure, improve engineering reliability while controlling costs, and is suitable for industrial production, overcoming the bottleneck of difficulty in improving existing thermal fatigue performance.

Claims

1. A nickel-based alloy with excellent high-temperature thermal fatigue properties, characterized in that, Its preparation method includes the following steps: (1) Boron powder and cobalt-niobium alloy powder are mixed at a mass ratio of 13-16:24-27 at a rotation speed of 90-120 r / min for 6-12 h to obtain powder mixture A; the particle size of the cobalt-niobium alloy powder is 30-220 micrometers and the particle size of the boron powder is 3-25 micrometers. (2) The powder mixture A obtained in step (1) is sent into a high-frequency induction plasma device and subjected to plasma reaction under pure argon protection. Finally, after argon rapid cooling treatment, intermediate alloy powder B containing cobalt-coated niobium diboride nanoparticles is obtained. The plasma reaction has the following characteristics: reaction pressure of 0.08-0.15 MPa, reaction temperature of 4800-5200℃, output power of 15-95 kW, and power supply operating frequency of 1.7-6.9 MHz; the cobalt-coated niobium diboride nanoparticles contained in the intermediate alloy powder B have an average particle size of 40-120 nanometers. (3) The nickel-based high-temperature alloy is heated to 1490–1530℃ under vacuum to form an alloy melt; the alloy melt is mixed with the intermediate alloy powder B obtained in step (2), and then melted and stirred at 1530℃–1680℃. After casting under argon protection, a nickel-based alloy ingot containing niobium diboride nanoparticles is obtained. The stirring speed is 350–650 r / min and the stirring time is 6–20 min. The mass ratio of the intermediate alloy powder B to the alloy melt is 0.009–0.1 wt.%:1; (4) The nickel-based alloy ingot containing niobium diboride nanoparticles obtained in step (3) is subjected to homogenization treatment, hot forging, solution treatment and two-stage aging treatment in sequence to obtain a nickel-based alloy with excellent high-temperature thermal fatigue performance. The homogenization process involves holding the temperature at 1160–1195℃ for 4–10 hours. The hot forging is carried out at 1050–1130°C with a forging ratio of 10–16:

1. The solution treatment involves holding at 1120–1180℃ for 50–120 minutes followed by water cooling. The two-stage aging treatment involves holding at 760–820℃ for 6–12 hours followed by air cooling, and then holding at 650–720℃ for 10–24 hours followed by air cooling. The nickel-based alloy with excellent high-temperature thermal fatigue performance exhibits superior thermal fatigue properties at high temperatures. By mass percentage, it is composed of the following components: C: 0.01–0.09%; Cr: 16.0–25.0%; Co: 12.0–25.0%; Mo: 4.1–7.8%; W: 0.4–2.8%; Ti: 1.1–2.9%; Al: 0.10–0.95%; Fe: ≤1.6%; Mn: ≤0.80%; Si ≤0.90%; P ≤0.060%; S ≤0.070%; B: 0.03–0.08%; Nb: 0.025–0.085%; balance Ni. The nickel-based alloy with excellent high-temperature thermal fatigue performance contains niobium diboride nanoparticles with a size of 35-210 nm and a mass percentage of 0.01%-0.09%. The nickel-based alloy exhibiting excellent high-temperature thermal fatigue performance, after 2000-4000 thermal cycles at 20-800℃, has a main crack length of 4.2-11.5 micrometers. Thermal fatigue failure is mainly controlled by crack initiation and crack propagation, and the main crack length is the key parameter characterizing thermal fatigue failure, directly affecting the service life of the material. The main crack length typically increases with increasing temperature and the number of thermal cycles. Therefore, the main crack length can effectively characterize the degree of thermal fatigue damage to the material and can serve as an important basis for evaluating the quality of thermal fatigue performance. The shorter the main crack length, the better the thermal fatigue performance. Compared with the prior art, the main crack length obtained by this invention is shorter, thus exhibiting better fatigue resistance. Furthermore, the number of cracks in this invention is far less than that in the prior art, showing a diffuse distribution, while the prior art exhibits a dense distribution.

2. The nickel-based alloy with excellent high-temperature thermal fatigue performance according to claim 1, characterized in that, In step (1), the particle size of the cobalt-niobium alloy powder is 60-200 micrometers, and the particle size of the boron powder is 4-23 micrometers.

3. The nickel-based alloy with excellent high-temperature thermal fatigue performance according to claim 1, characterized in that, The plasma reaction described in step (2) has the following characteristics: reaction pressure is 0.09-0.14 MPa, reaction temperature is 4875-5125℃, output power is 19-90 kW, and power supply operating frequency is 1.9-6.7 MHz; the average particle size of niobium diboride particles in the intermediate alloy powder B is 42-115 nanometers.

4. The nickel-based alloy with excellent high-temperature thermal fatigue performance according to claim 1, characterized in that, In step (3), the mass ratio of intermediate alloy powder B to alloy melt is 0.035–0.07 wt.%:

1.

5. The nickel-based alloy with excellent high-temperature thermal fatigue performance according to claim 1, characterized in that, The chemical composition of the nickel-based alloy with excellent high-temperature thermal fatigue performance described in step (4) is as follows (by mass percentage): C: 0.03–0.08%; Cr: 18.0–22.0%; Co: 15.0–22.0%; Mo: 4.5–7.5%; W: 0.5–2.5%; Ti: 1.6–2.8%; Al: 0.20–0.80%; Fe≤1.0%; Mn≤0.50%; Si≤0.50%; P≤0.020%; S≤0.010%; B: 0.03–0.075%; Nb: 0.026–0.083%; balance Ni; The nickel-based alloy with excellent high-temperature thermal fatigue performance contains niobium diboride nanoparticles with a size of 39-208 nm and a mass percentage of 0.015%-0.085%.

6. The nickel-based alloy with excellent high-temperature thermal fatigue performance according to claim 1, characterized in that, Step (4) yields a nickel-based alloy with excellent high-temperature thermal fatigue performance. After 2500-3500 thermal cycles at 20-800℃, the length of the main crack in the alloy is 4.6-9.3 micrometers.